2021
DOI: 10.3390/biomechanics1010010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Biomechanical Study of Screw Fixation Techniques in Periacetabular Osteotomy

Abstract: Periacetabular osteotomy (PAO) is a common surgical treatment for developmental dysplasia of the hip. To obtain the optimal method of fixation during PAO, different screw fixation techniques have been proposed for stabilizing the acetabular fragment. This study assesses the biomechanical performance of two popular 3-screw fixation techniques: iliac (IS) and transverse (IT) configurations, through finite element simulations. Additionally, different 2-screw combinations are simulated to investigate the biomechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…During the surgery, intraoperative osteotomy requires internal fixation to maintain stabilization of the acetabular fragment. The IS and TS internal fixation techniques are the mainstream approaches used in PAO, and various clinical and mechanical studies, ranging from in vitro experiments to simulations, have been reported ( Babis et al, 2002 ; Yassir et al, 2005 ; Mechlenburg et al, 2007 ; Widmer et al, 2010 ; Bakhtiarinejad et al, 2021 ; Leopold et al, 2021 ). However, those mechanical research studies were limited due to the lack of realistic gait simulation, and muscle force that should contribute to the deformation and stress of the bone was not represented in models, leading to underreported FE results ( Chen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the surgery, intraoperative osteotomy requires internal fixation to maintain stabilization of the acetabular fragment. The IS and TS internal fixation techniques are the mainstream approaches used in PAO, and various clinical and mechanical studies, ranging from in vitro experiments to simulations, have been reported ( Babis et al, 2002 ; Yassir et al, 2005 ; Mechlenburg et al, 2007 ; Widmer et al, 2010 ; Bakhtiarinejad et al, 2021 ; Leopold et al, 2021 ). However, those mechanical research studies were limited due to the lack of realistic gait simulation, and muscle force that should contribute to the deformation and stress of the bone was not represented in models, leading to underreported FE results ( Chen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FE method has been proven to be useful for postoperative modeling of different orthopedic applications and has been used to evaluate different fixation methods for PAO [ 20 , 27 , 28 ]. Despite TPO being a mainstay of advanced surgical treatment of multiple conditions, FE analysis has, to our knowledge, not previously been applied to evaluate the stability of different implant constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the study demonstrated the comparison of different fixation systems, the modeling had its limitations. Similar to other established finite element models of the pelvis [ 28 ], the implant screws were simplified as homogeneous with isotropic materials. Furthermore, a constant cortical thickness and homogeneous and isotropic material properties were assigned to the pelvis bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other established finite element models of the pelvis [60], the implant screws were simplified as cylindrical solids with no threads to avoid singularities at sharp edges or notches with a very small radius. However, since the aim of this study is to compare the biomechanical performance of different fixation techniques and identical simplifications are applied, it is unlikely that modeling of the threads would change the outcome.…”
Section: Discussionmentioning
confidence: 99%